2020
DOI: 10.3389/fnins.2020.00692
|View full text |Cite
|
Sign up to set email alerts
|

Brain Computer Interfaces for Improving the Quality of Life of Older Adults and Elderly Patients

Abstract: All people experience aging, and the related physical and health changes, including changes in memory and brain function. These changes may become debilitating leading to an increase in dependence as people get older. Many external aids and tools have been developed to allow older adults and elderly patients to continue to live normal and comfortable lives. This mini-review describes some of the recent studies on cognitive decline and motor control impairment with the goal of advancing non-invasive brain compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(62 citation statements)
references
References 63 publications
0
53
0
Order By: Relevance
“…These results could be useful to improve the quality of life by carrying out prospective memory training in older adults. Recently, brain computer interface is being one of the most popular technologies to improve the quality of life among older adults by enhancing or repairing their cognitive function and motor function [ 40 ]. Some studies have revealed the brain computer interface training system could improve memory and attention in older adults [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results could be useful to improve the quality of life by carrying out prospective memory training in older adults. Recently, brain computer interface is being one of the most popular technologies to improve the quality of life among older adults by enhancing or repairing their cognitive function and motor function [ 40 ]. Some studies have revealed the brain computer interface training system could improve memory and attention in older adults [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In related works, P300 ERP component was used for brain computer interface study [ 25 27 ], the ERP components in this study also can be used to build an affective brain computer interface. BCI also can be very useful for the elder people [ 28 31 ]. To improve BCI performance for daily-life use, advanced classification methods are required [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, output-type BMI has been gaining interest in recent years as a tool for supporting the daily activities of persons who have difficulty with independent living or spontaneous expression due to disease, disability, or aging. Specifically, it will soon become possible to operate a variety of assistive devices, including wheel chairs, exoskeletons, drones, and communication robots using the operator's EEG signals (Figure 3) [54]. Researchers are also EEG Measurement as a Tool for Rehabilitation Assessment and Treatment DOI: http://dx.doi.org /10.5772/intechopen.94875 developing and exploring the effectiveness of smart homes that incorporate these BMI technologies [55].…”
Section: Brain-machine Interface (Bmi)mentioning
confidence: 99%
“…An overview of already used protocols of frequency EEG-neurofeedback training with the references to exemplary studies and their main therapeutic purpose [53]. EEG-based BMI for assisting with daily activities and improving quality of life [54].…”
Section: ↑ Gamma Training Of Cognitive Control;mentioning
confidence: 99%
See 1 more Smart Citation